Molecular Mechanisms Governing the Stem Cell’s Fate in Brain Cancer: Factors of Stemness and Quiescence - Gulaia, Valeriia; Kumeiko, Vadim; Shved, Nikita; Cicinskas, Eduardas; Rybtsov, Stanislav; Ruzov, Alexey; Kagansky, Alexander (Frontiers in Cellular Neuroscience, 2018)
Cellular quiescence is a reversible, non-cycling state controlled by epigenetic, transcriptional, and niche-associated molecular factors. Quiescence is a condition where molecular signaling pathways maintain the poised cell-cycle state whilst enabling rapid cell cycle re-entry. To achieve therapeutic breakthroughs in oncology it is crucial to decipher these molecular mechanisms employed by the cancerous milieu to control, maintain and gear stem cells towards re-activation. Cancer stem cells have been extensively studied in most malignancies, including glioma. Here, the aberrant niche activities skew the quiescence/activation equilibrium, leading to rapid tumor relapse after surgery and/or chemotherapy. Unraveling quiescence mechanisms promises to afford prevention of (often multiple) relapses, a key problem in current glioma treatment. This review covers the current knowledge regarding normal and aberrant cellular quiescence control whilst also exploring how different molecular mechanisms and properties of the neighboring cells can influence the molecular processes behind glioma stem cell quiescence..